2009
DOI: 10.1515/cclm.2009.310
|View full text |Cite
|
Sign up to set email alerts
|

Impaired anti-inflammatory function of apolipoprotein A-II concentrations predicts metabolic syndrome and diabetes at 4 years follow-up in elderly Turks

Abstract: Background: We evaluated prospectively the predictive value of serum apolipoprotein (apo) A-II, the second major apolipoprotein of high-density lipoprotein (HDL), for cardiometabolic risk in Turkish adults showing abnormalities in other proteins that normally confer protection. Methods: Determinants of apoA-II and its associations with coronary heart disease (CHD), metabolic syndrome (MetS) and diabetes were investigated at 4 years follow-up in 193 elderly men and women. Results: ApoA-II concentrations at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…However, the results of a current study showed that in vitro HDLs isolated from plasma of human apoA-II transgenic rabbits compared to normal rabbits had stronger activity for cholesterol efflux and stronger suppressive effects on inflammatory cytokines expression by macrophages (Wang et al, 2013). Also, in other studies, increased serum ApoA-II concentration has been introduced as a protective factor against CVD, hyperlipidemia, and metabolic syndrome (Birjmohun et al, 2007;Onat, G H, Ayhan, Ugur, & Can, 2009;Parra et al, 1992;Roselli della Rovere et al, 2003;Won Yi et al, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…However, the results of a current study showed that in vitro HDLs isolated from plasma of human apoA-II transgenic rabbits compared to normal rabbits had stronger activity for cholesterol efflux and stronger suppressive effects on inflammatory cytokines expression by macrophages (Wang et al, 2013). Also, in other studies, increased serum ApoA-II concentration has been introduced as a protective factor against CVD, hyperlipidemia, and metabolic syndrome (Birjmohun et al, 2007;Onat, G H, Ayhan, Ugur, & Can, 2009;Parra et al, 1992;Roselli della Rovere et al, 2003;Won Yi et al, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Onat et al [13] showed that low serum apoA-II concentrations appear to predict incident MetS (relative risk, 3.5) and type 2 diabetes mellitus (relative risk, 4.5) in both sexes at an increment of 1 standard deviation, which is consistent with previous studies [6-9]; however, increased apoA-II values were not associated with prevalent or incident CHD and tended to be marginally atheroprotective only in males. In our study, the prevalence of Mets decreased as the quartiles of apoA-I increased, and increased with increasing quartiles of apoB, but there were no significant differences in MetS percentage between quartiles of apoA-II.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Onat et al [13] showed that low serum apoA-II concentrations confer risk of metabolic syndrome (MetS) and type 2 diabetes mellitus among Turkish adults at 4 years follow-up. There are few studies about the association between apoA-II and MetS, a constellation of atherosclerotic cardiovascular disease risk factors [14], and the possible properties of apoA-II in cardiovascular risk are even less clear, especially in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 Da ha son ra hal kı mız da be lir li ko ru yu cu pro te in ler de (baş ta HDL par ça cık la rı 5 ve üze rin de bu lu nan apo li pop ro te in [apo] A-I, A-II ve C-III ol mak üze re) ate rop ro tek tif ve an ti-inf la matu var ni te lik le ri nin kay bı na bağ lı ola rak di ya bet ve KKH gi bi kar di yo me ta bo lik has ta lık lar dan ye terin ce ko ru ma dı ğı göz lem len di. [6][7][8] Bir ge nel po pü -las yon da ilk de fa ta nım la nan bu ko ru yu cu pro te in dis fonk si yo nu -ke sin bi lin me mek le bir lik te-ye tiş -kin le ri miz de art mış pro-inf la ma tu ar du rum ve/veya ok si da tif stres sü re ci ne at fe dil miş ti. Anı lan sü re cin ya kın iliş ki li bu lun du ğu (ab do mi nal) obe zite den bir öl çü de ba ğım sız ol du ğu gö rül dü ğün den 5,6 ve kan da trig li se rid/HDL-ko les te rol ora nı nın özel-lik le ka dın da pro-inf la ma tu var du rum ile ge niş öl-çü de öz deş leş ti ği (ya yın lan ma mış göz lem) sap tan dı ğın dan, kan da trig li se rid dü zey le ri miz de ye ni de ği şik lik le rin olup ol ma dı ğı nı araş tır ma ge reği ni duy duk.…”
Section: Türkiye'de Kandaki Trigliserid Düzeylerinde Halk Sağlığı Açıunclassified
“…Kan ko ru yu cu pro te inle rin de ku sur, (ab do mi nal) obe zi te ser gi le yen halkı mız da çe şit li yön le riy le bel ge len miş tir. [5][6][7][8] El de ki bul gu lar bu na bir açık la ma da ha ge tir mek te dir. Ça-lış ma nın on ye di yıl gi bi uzun ca bir dö nem de hem er kek ler de hem ka dın lar da yaş lan ma dan arın dır -ma yön te miy le ya pıl ma sı, iki alt dö ne min kar şı laş -tı rıl ma sı, Trg de ğer le ri nin hem no mi nal, hem de lo ga rit mik dö nü şüm uy gu la ya rak kı yas lan ma sı ça-lış ma nın güç lü yan la rı nı teş kil et mek te dir.…”
Section: Alin Ma Si Ge Re Ken öN Lem Lerunclassified